2017
DOI: 10.3844/ajavsp.2017.143.149
|View full text |Cite
|
Sign up to set email alerts
|

The Visceral Organ, Gastrointestinal Tract and Blood Characteristics in Pegagan Ducks Fed Ration Fermented by Tape Yeast with Different Moisture Content

Abstract: The purpose of this study was to assess the effect of administration diet containing locally sourced materials fermented by tape yeast with different moisture content on the weight of the visceral organs, gastrointestinal tract and blood chemistry and profile of Pegagan ducks. As many as 200 Pegagan ducks aged 3 days were kept for 6 weeks in colony cages. This study used a completely randomized design that consisted of 5 treatments and 4 replicates. The treatments tested were symbolized as P1, P2, P3, P4 and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…These findings agree with Kridtayopas et al [6] who reported decreased villus height in HSD broilers, and Kamel et al [35], who observed that HSD negatively affected duodenal histomorphometry. The decrease in VSA leads to reduce nutrient absorption and can also be linked with decreased intestinal weight [36], as observed in the current study. HSD stress leads to higher apoptosis and reduced epithelial cell proliferation.…”
Section: Intestinal Histomorphometry and Intra-epithelial Lymphocyte ...supporting
confidence: 77%
“…These findings agree with Kridtayopas et al [6] who reported decreased villus height in HSD broilers, and Kamel et al [35], who observed that HSD negatively affected duodenal histomorphometry. The decrease in VSA leads to reduce nutrient absorption and can also be linked with decreased intestinal weight [36], as observed in the current study. HSD stress leads to higher apoptosis and reduced epithelial cell proliferation.…”
Section: Intestinal Histomorphometry and Intra-epithelial Lymphocyte ...supporting
confidence: 77%
“…At the end of the experiment, all ducks were weighed to determine the live body weight. The measurement of the relative weight and length of the gastrointestinal tract (GIT) and internal organs (IO) refers to Yosi et al (2017). As many 2 birds in each treatment were randomly selected.…”
Section: Gastrointestinal Tract and Internal Organsmentioning
confidence: 99%
“…Measurement of blood hematological and serum biochemical parameters according to Yosi et al (2017). At the end of the experiment, as many 3 ml of venous blood samples from 2 birds per pen were collected by puncture of the brachial vein using sterilized syringes containing anticoagulant.…”
Section: Measurementsmentioning
confidence: 99%
“…The rapid spread of bacterial infection is facilitated by the bird's anatomical and physiological characteristics. The appearance of a pathological focus on the mucous membranes can have consequences throughout the body, including the gastrointestinal tract (Yosi et al, 2017). The complex therapy of parasitic diseases should be accompanied by monitoring of the gastrointestinal tract's functional state for the presence of bacterial infections (Dzhafarov et al, 2010;Plys, 2017;Zhanabayev et al, 2022).…”
Section: Introductionmentioning
confidence: 99%